Stories that Count: Influence of News Narratives on Issue Attitudes. (March 2014) - Shen, Fuyuan; Ahern, Lee; Baker, Michelle
This paper examines the impact of using narratives to frame a political issue on individuals' attitudes. In an experiment, we asked participants to read either narrative or informational news articles that emphasized the potential economic benefits or environmental consequences associated with shale gas drilling. Results indicated both news formats (narrative vs. informational) and frames (environmental vs. economic) had significant immediate effects on issue attitudes and other responses; narrative environmental news had a significantly greater impact than informational environmental news. Cognitive responses and empathy were significant partial mediators of narrative impact. Environmental narratives also had a more significant impact on individuals' delayed issue attitudes.